Practical big data analytics : hands-on techniques to implement enterprise analytics and machine learning using Hadoop, Spark, NoSQL and R /: hands-on techniques to implement enterprise analytics and machine learning using Hadoop, Spark, NoSQL and R. (2018) - Dasgupta, Nataraj
No abstract available